Ultrasonographic study of female perineal body and its supportive function on pelvic floor - Zhou, Minzhi; Shui, Wen; Bai, Wenkun; Wu, Xing; Ying, Tao (Frontiers in Medicine, 2023)
Abstract Objectives: The study aimed to observe, measure the size and elastic value of perineal body (PB) and assess its association with levator hiatus. Methods: Datasets were acquired in 45 nulliparous, 66 POP women and 70 postpartum women using ultrasound. The PB was measured in depth, height, and Young’s modulus. The datasets were compared to assess whether there are some differences in the morphology, dimension and elastography modulus of PB among women. Pearson correlation analysis was used to evaluate the association between the morphology measurements (ΔValsalva-rest[v-r]), tissue mechanical properties (ΔValsalva-rest[v-r]) of the PB and levator hiatus area (ΔValsalva-rest[v-r]) to preliminarily explore whether PB can influence levator hiatus. Results: Four representative manifestations of PB were presented in our study. Nulliparous women had smaller diameters and bigger Young’s modulus while postpartum women had bigger diameters and smaller Young’s modulus. POP and postpartum women had bigger levator hiatal distensibility and PB extensibility. There was no statistical association between PB measurements and levator hiatal area. Conclusions: It is feasible to observe the morphology of PB and assess the dimension and elastography modulus by high-frequency ultrasound. The manifestations and measurements of PB are influenced by parity and long-term increased abdominal pressure. Our study preliminarily shows that PB has little effect on levator hiatus area.